The Future of Flexible Product Manufacturing by Using Industry 4.0 Technologies in Regard to Consumer Preferences - Ejaz, Muhammad Rahim (Marketing & Menedzsment, 2021)
THE AIMS OF THE PAPER The core objectives of this paper are to understand constantly changing consumer choices over time and the manufacturing of flexible products to answer the problem. The flexible products with multiple utility choices can help consumers from every segment to fulfil their needs. The study has shed light on the flexible product manufacturing process and has also discussed launching strategies into the market with having considered various market factors in the process. METHODOLOGY A rigorous analysis of literature has been done to understand why flexible products should be preferred over standard products. Literature related to flexible product strategy is being examined and explored its dimensions of price setting and product utility. MOST IMPORTANT RESULTS This study provides a road map for companies to shift their focus on developing new manufacturing processes in order to develop flexible products to address dynamic consumer preferences. This study also shed light on the fact the flexible products might be more profitable for the company. RECOMMENDATIONS The findings show that flexible products provide larger range of utility choices and with a right price; it can be more profitable than a standard product. Flexible products can go along with mass customisation of products which can enlarge utility choices for consumers to an unlimited level.